Composition and function of the C1b/C1f region in the ciliary central apparatus - Ewa Joachimiak (Nature Portfolio, 2021)
Abstract Motile cilia are ultrastructurally complex cell organelles with the ability to actively move. The highly conserved central apparatus of motile 9 × 2 + 2 cilia is composed of two microtubules and several large microtubule-bound projections, including the C1b/C1f supercomplex. The composition and function of C1b/C1f subunits has only recently started to emerge. We show that in the model ciliate Tetrahymena thermophila, C1b/C1f contains several evolutionarily conserved proteins: Spef2A, Cfap69, Cfap246/LRGUK, Adgb/androglobin, and a ciliate-specific protein Tt170/TTHERM_00205170. Deletion of genes encoding either Spef2A or Cfap69 led to a loss of the entire C1b projection and resulted in an abnormal vortex motion of cilia. Loss of either Cfap246 or Adgb caused only minor alterations in ciliary motility. Comparative analyses of wild-type and C1b-deficient mutant ciliomes revealed that the levels of subunits forming the adjacent C2b projection but not C1d projection are greatly reduced, indicating that C1b stabilizes C2b. Moreover, the levels of several IFT and BBS proteins, HSP70, and enzymes that catalyze the final steps of the glycolytic pathway: enolase ENO1 and pyruvate kinase PYK1, are also reduced in the C1b-less mutants.